Lagrangian Support Vector Machines - Musicant, David; Mangasarian, Olvi (My University, 2000)
An implicit Lagrangian for the dual of a simple reformulation of the standard quadratic program of a linear support vector machine is proposed. This leads to the minimization of an unconstrained di erentiable convex function in a space of dimensionality equal to the number of classi ed points. This problem is solvable by an ex- tremely simple linearly convergent Lagrangian support vector machine (LSVM) algorithm. LSVM requires the inversion at the outset of a single matrix of the order of the much smaller dimensionality of the original input space plus one. The full algorithm is given in this paper in 11 lines of MATLAB code without any special optimization tools such as linear or quadratic programming solvers. This LSVM code can be used \as is" to solve classi cation problems with millions of points. For example, 2 million points in 10 dimensional input space were classi ed by a linear surface in 82 minutes on a Pentium III 500 MHz notebook with 384 megabytes of memory (and additional swap space), and in 7 minutes on a 250 MHz UltraSPARC II processor with 2 gigabytes of memory. Other standard classi cation test problems were also solved. Nonlinear kernel classi cation can also be solved by LSVM. Although it does not scale up to very large problems, it can handle any positive semide nite kernel and is guaranteed to converge. A short MATLAB code is also given for nonlinear kernels and tested on a number of problems.